2018
DOI: 10.3389/fpls.2018.00373
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Phosphorus Supply on Selenium Uptake During Hydroponics Experiment of Winter Wheat (Triticum aestivum) in China

Abstract: Selenium (Se) is a necessary trace element for humans and animals, and Se fertilization is an efficient way to increase Se concentration in the edible parts of crops, thus enhance the beneficiary effects of Se in human and animal health. Due to the similarity of physical and chemical properties between phosphate () and selenite (), phosphorus (P) supply often significantly impacts the absorption of Se in plants, but little is known about how P supply influences the subcellular distribution and chemical forms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
6
13
0
Order By: Relevance
“…Ionome‐wide information is also important when studying the consequences of evolution on the flow of nutrients between organisms and their environment, as the availability, uptake, and utilization of specific macronutrients is often dependent on the dynamics of trace elements (Lind & Jeyasingh ; Liu et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ionome‐wide information is also important when studying the consequences of evolution on the flow of nutrients between organisms and their environment, as the availability, uptake, and utilization of specific macronutrients is often dependent on the dynamics of trace elements (Lind & Jeyasingh ; Liu et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Increased elemental resolution provides an enhanced ability to identify the axes of ecologically relevant variation among populations, which could be useful in identifying the phenotypic underpinnings of local adaptation (Huang & Salt 2016;Goos et al 2017). Ionome-wide information is also important when studying the consequences of evolution on the flow of nutrients between organisms and their environment, as the availability, uptake, and utilization of specific macronutrients is often dependent on the dynamics of trace elements (Lind & Jeyasingh 2018;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2014) reported that OsPT2, a phosphate transporter, is involved in selenite uptake, thereby indicating that a competitive relationship might exist between P and Se. Studies of wheat have also suggested that selenite absorption in plants was suppressed by increasing P supply (Liu et al, 2018) and was stimulated by P deficiency (Li et al, 2008). However, the contradictory results demonstrated that P supply elevated the Se concentration in alfalfa (Carter et al, 1972) and berseem (Singh and Malhotra, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, sufficient knowledge of Se speciation in plants is required when assessing the effects of Se biofortification in humans. Recently, Liu et al (2018) adopted a sequential extraction method to determine the chemical forms of Se in wheat plants. However, these forms are considerably different from the actual Se species associated with Se metabolism compounds in plant tissues that can be extracted by enzymatic hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies we demonstrated that increasing the P supply decreased the Se concentration in all tissues and the transport of Se from root to shoot in winter wheat seedlings. These effects of increasing P, observed during a hydroponic experiment, were due to the inhibited absorption of Se, the inhibited distribution of Se in the root cell wall and the enhanced distribution of Se in root soluble fractions (such as vacuoles) by P supply ( Liu et al., ). The objectives of the present study were to further investigate the interactive effects of P and Se application on: (1) the concentrations and ratios of organic and inorganic Se, (2) the Se‐protein, Se‐nucleic acid and Se‐polysaccharide concentrations and their shares in the organic Se fraction, and (3) the Se concentrations in albumin, glutenin, gliadin and globulin protein subfractions, and their shares in the Se‐protein in grains of winter wheat.…”
Section: Introductionmentioning
confidence: 99%